Ellis Van Creveld syndrome - Shilpy S; Nikhil M; Samir D (Wolters Kluwer Medknow Publications, 2007)
Ellis Van Creveld syndrome is a rare disorder and is a form of short-limbed dwarfism. It is an autosomal recessive disorder characterized by tetrad of disproportionate dwarfism, post-axial polydactyly, ectodermal dysplasia and heart defects. This case report presents a classical case of a seven-year-old boy with Ellis Van Creveld syndrome presented with discrete clinical findings.